2017
DOI: 10.1051/sicotj/2017026
|View full text |Cite
|
Sign up to set email alerts
|

Management of acetabular fractures in the geriatric patient

Abstract: Introduction: Open reduction and internal fixation (ORIF) is standard care for most acetabular fractures. With increasing numbers of acetabular fractures in the elderly, the risk of revision surgery and conversion to total hip replacement (THR) is increasing. Alarmingly, about 20–25% of acetabular fractures in the elderly following ORIF needed revision and conversion to delayed THR. Methods: Recently, prognostic factors have been identified, which correlate with an increased risk of worse outcomes following OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
0
36
0
1
Order By: Relevance
“…A literature search revealed few publications on both highand low-energy geriatric acetabular fracture outcomes. 4,8,[20][21][22] Two of these studies found high-energy fracture patterns to follow similar fracture patterns as the low-energy group, resulting in a majority anterior wall or both column fractures. 8,21 Also, prior studies demonstrate that posterior wall fracture patterns are found to be associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…A literature search revealed few publications on both highand low-energy geriatric acetabular fracture outcomes. 4,8,[20][21][22] Two of these studies found high-energy fracture patterns to follow similar fracture patterns as the low-energy group, resulting in a majority anterior wall or both column fractures. 8,21 Also, prior studies demonstrate that posterior wall fracture patterns are found to be associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Conservative treatment is the most suitable option in case of a non-displaced acetabular fracture. Non-surgical treatment can also be considered in dislocated acetabular fractures with anterior column involvement or in intrinsically stable injuries such as transverse type fractures [22][23][24][25]. Complications of conservative treatment or minimally invasive procedures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…traction or external fixation) include amyotrophy, pressure ulcers, deep venous thrombosis, pin tract infection and increased mortality. Most importantly, the likelihood of attaining an acceptable acetabular reduction by traction alone is small [1,7,10,19,20,22,23,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of injury in acetabular fractures is road traffic accidents and fall from a height [1,2]. Usually acetabular fractures are associated with other major visceral injuries.…”
Section: Clinical Featuresmentioning
confidence: 99%